1967
DOI: 10.1172/jci105580
|View full text |Cite
|
Sign up to set email alerts
|

Blood Cholesterol and Hydrocortisone Production in Man: Quantitative Aspects of the Utilization of Circulating Cholesterol by the Adrenals at Rest and under Adrenocorticotropin Stimulation*

Abstract: Summary. A kinetic study of the conversion of blood cholesterol into hydrocortisone was carried out in two patients through prolonged infusions of cholesterol-4-14C. The following points appear to be established by our observations:1) The infused tracer behaved metabolically like endogenous cholesterol; it could therefore serve as a means of labeling plasma cholesterol for investigating its utilization by the adrenal cortex.2) At rest, about 80% of hydrocortisone derived from plasma cholesterol, the other 20% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
2

Year Published

1970
1970
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(37 citation statements)
references
References 25 publications
1
34
0
2
Order By: Relevance
“…The fi rst and rate-limiting step is the formation of pregnenolone from cholesterol. At rest and during stress about 80 % of circulating cortisol is derived from plasma cholesterol: the remaining 20 % is synthesized in situ from acetate and other precursors 91 . Experimental studies suggest that HDL is the preferred cholesterol source of steroidogenic substrate in the adrenal gland 92 .…”
Section: Clinical Consequences Of Hypocholesterolemiamentioning
confidence: 99%
“…The fi rst and rate-limiting step is the formation of pregnenolone from cholesterol. At rest and during stress about 80 % of circulating cortisol is derived from plasma cholesterol: the remaining 20 % is synthesized in situ from acetate and other precursors 91 . Experimental studies suggest that HDL is the preferred cholesterol source of steroidogenic substrate in the adrenal gland 92 .…”
Section: Clinical Consequences Of Hypocholesterolemiamentioning
confidence: 99%
“…Adrenal tissue may serve as a useful model for studying these mechanisms because studies in man (1,2) and the rat (3,4) showed that 80% or more of the cholesterol substrate for adrenal steroidogenesis may come from plasma. However, little is known about the process by which extracellular cholesterol enters the adrenal cells.…”
mentioning
confidence: 99%
“…Moreover in man (Borkowski, Levin, Delcroix, Mahler & Verhas, 1967) and in the guinea-pig (Werbin & Chaikoff, 1961) it was demonstrated that the proportion of cholesterol derived from the plasma at rest, 80% in man and 60% in the guinea-pig, was not altered by administration of ACTH. Oestrogen treatment does decrease plasma cholesterol concentrations (Boyd & McGuire, 1956) and the resulting hypofunction of the adrenal during stress can be instantaneously restored to normal by intravenous infusion of plasma from normal but not from hexoestrol treated rats (Holzbauer & Vogt, 1957a).…”
Section: Discussionmentioning
confidence: 99%
“…Oestrogen treatment does decrease plasma cholesterol concentrations (Boyd & McGuire, 1956) and the resulting hypofunction of the adrenal during stress can be instantaneously restored to normal by intravenous infusion of plasma from normal but not from hexoestrol treated rats (Holzbauer & Vogt, 1957a). To the author's knowledge there are no reports on the effect of ACTH on plasma cholesterol levels, but since ACTH has been shown to accelerate the metabolism of plasma and adrenal cholesterol into hydrocortisone (Borkowski et al, 1967) and not to stimulate cholesterol synthesis, a decrease in plasma cholesterol might be expected.…”
Section: Discussionmentioning
confidence: 99%